The Belly Burn Plan : 6 weeks to a lean, fit and healthy body - Mitchell, Traci D. (Harlequin, 2015)
"Personal trainer and weight loss coach Traci D Mitchell helps readers say goodbye to unsightly and lethal belly fat with [a] ... diet and exercise program rooted in body type-specific eating, high intensity interval training (HIIT), and healthy lifestyle choices"--